STUDIES OF A MYXOVIRUS RECOVERED FROM PATIENTS WITH INFECTIOUS HEPATITIS : II. FINE STRUCTURE AND ELECTRON MICROSCOPIC DEMONSTRATION OF INTRACYTOPLASMIC INTERNAL COMPONENT AND VIRAL FILAMENT FORMATION - Prose, Philip H. (The Rockefeller University Press, 1965)
WB virus has been shown to have a fine structure which is characteristic of members of the mumps-NDV-parainfluenza group of viruses. Viral internal component has been demonstrated within the cytoplasm of infected cells. The incorporation of internal component into virus filaments at the cell surface has also been demonstrated. The evidence presented suggests that virus filament formation occurs by a process of invagination of the cell membrane about the coiled strands of internal component lying beneath the membrane.